Description of two new spider species from Ecuadorian caves, along with a note on the distribution of Plato troglodita Coddington, 1986 (Araneae, Theridiosomatidae) - Dupérré, Nadine; Tapia, Elicio (Zootaxa, 2025)
Two new cave spider species belonging to the family Theridiosomatidae are described from the Ecuadorian Amazonian ecoregion: Plato leodani sp. nov. (male, female), and Plato shaime sp. nov. (male, female). Images of the type specimens of Plato troglodita Coddington, 1986 are included and its distribution is updated, being restricted to the type locality in Morona Santiago Province, Ecuador. Finally, the specimens identified as Plato troglodita by Prete & Brescovit (2024) are considered a misidentification.